Injection currents in lamellar crystals of gallium telluride - Madatov, R.S.; Tagiyev, T.B.; Gabulov, I.A.; Abbasova, T.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
The results of researches of electrical properties and injection currents in lamellar samples of p-type gallium telluride with the purpose of determination of charge transfer mechanism both in the Ohm law regime and in the range of its violation in the wide temperature interval (77- 300) K have been given. Specific resistance of the studied samples changed within 5·10⁴ 6·10⁵ Ohm·cm at room temperatures. The analysis based on the Lampert theory has shown that the current-voltage characteristics at 77 K are in accord with monopolar injection current and one discrete level in the gallium telluride bandgap with the energy 0.18 eV and concentration 5.6·10¹² cm⁻³. It has been found that, in the temperature range of 77- 300 K in GaTe single crystals, the mechanism of charge transfer can be ascertained with currents limited by the spatial charge.